DOES THE VOLATILE HYDROCARBON PROFILE DIFFER BETWEEN THE SEXES: A CASE STUDY ON FIVE APHIDOPHAGOUS LADYBIRDS. Issue 3 (25th July 2014) - Pattanayak, Rojalin; Mishra, Geetanjali; Omkar; Chanotiya, Chandan Singh; Rout, Prasant Kumar; Mohanty, Chandra Sekhar
<x xml:space="preserve">Abstract</x> Insect hydrocarbons (HCs) primarily serve as a waterproofing cuticular layer and function extensively in chemical communication by facilitating species, sex, and colony recognition. In this study, headspace solid‐phase microextraction is employed for investigating the sex‐specific volatile HC profile of five ladybirds collected from Lucknow, India namely, Coccinella septempunctata (L.), Coccinella transversalis (Fabr.), Menochilus sexmaculatus (Fabr.), Propylea dissecta (Mulsant), and Anegleis cardoni (Weise) for the first time. Major compounds reported in C. septempunctata, C. transversalis, and A. cardoni are methyl‐branched saturated HCs, whereas in M. sexmaculatus, and P. dissecta, they are unsaturated HCs. Other than A. cardoni, both the sexes of the other four ladybirds had similar compounds at highest peak but with statistically significant differences. However, in A. cardoni, which is a beetle with a narrow niche, the major compound in both male and female was different. The difference in volatile HC profile of the sexes of the five ladybirds indicates that gender‐specific differences primarily exist due to quantitative differences in chemicals with only very few chemicals being unique to a gender. This variation in semiochemicals might have a role in behavioral or ecological aspects of the studied ladybirds.